Association of Deslorelin and Sulpiride for Double Ovulation Induction in Mares - Bertoldi, Ariel [UNESP]; Segabinazzi, Lorenzo Garrido [UNESP]; Freitas Dell'Aqua, Camila de Paula [UNESP]; Dell'Aqua Junior, Jose Antonio [UNESP]; Alvarenga, Marco Antonio [UNESP] (Elsevier, 2018)
The aim of this study was to verify the effect of deslorelin and sulpiride association on double ovulation induction in mares. Ten mares were used for this study. Eight days after ovulation, luteolysis was induced and mares were submitted a daily ultrasonographic evaluation until observation of at least two follicles measuring between 20 and 25 mm. Animals were split in two experimental groups in a crossover study. In deslorelin (DES) group, the animals received 150 μg deslorelin, intramuscularly, every 12 hours, until the second largest follicle reached at least 33 mm in diameter, at which time ovulation induction was performed with 1.500 IU of human chorionic gonadotrophin, IV. In the DES + sulpiride (SULP) group, the treatment was performed in the same manner as in the DES group, associated with the administration of 1 g of sulpiride, orally, once daily until the time of ovulations induction. In both groups, ultrasound examinations were performed daily to evaluate follicular development and the detection of ovulations. Double ovulations were observed in 70% (7/10) of the animals of the DES group and 50% (5/10) of the animals in the DES + SULP group. The percentage of ovulations corresponding to the number of follicles developed was 81.8% (18/22) for the DES group and 79% (15/19) for the DES + SULP group, and no difference was observed between the groups (P >.05). We conclude that association of sulpiride with deslorelin acetate did not contribute to the increase in double ovulations in mares.
Keywords: antidopaminergic; dopamine; Equine; GnRH; superovulation